0089 Development of a kss wide multidisciplinary, multi-tiered simulation faculty development programme: Teachsim faculty. (2nd November 2015) - Lomax, Suzi; Bygrave, Celia; Featherstone, Barry; Moran, Paul
Abstract : The majority of our trusts have an established simulation service. However, faculty recruitment and training are challenging. Faculty vary in their experience and knowledge of simulation. Expanding the pool of suitably trained simulation facilitators from all healthcare disciplines across HEKSS is required for ongoing delivery. There are limited guidelines or standards for training for those delivering simulation based training, 1 and it is now well recognised that this type of medical education requires particular experience and skills. 2 We have devised a multi-tiered, multi-centred training programme through a combination of day courses and practical mentorship aimed at all healthcare workers within KSS. The programme also enables local Simulation leads to direct their new faculty to attend courses that meet their level of training needs through a course structure allowing different points of entry. The programme requires candidates to deliver simulation locally to gain certification and allows quality assured training and cross pollination of ideas. This will strengthen the network of simulation providers across the region and establish a consistent standard of training. Level 1 develops knowledge, skills and behaviour to enable healthcare workers to undertake simulation faculty roles. The training emphasises educational theory behind simulation, scenario development, the basics of equipment and an introduction to debriefing followed by a practical component. Level 2 develops the skills required to debrief in a simulation environment. This day mixes theory with practical sessions and aims to encourage improved observational skills, and confidence in debriefing. Level 3 provides experienced faculty members with the skills required to deliver and develop simulation courses to meet local needs. This is accompanied by one to one mentorship following the course to enable delivery of simulation based programmes. This quality assured training will ensure that novel, tailored multidisciplinary simulation based learning events are developed and existing programmes are sustainable across KSS. References: Cumin D, Merry AF, Weller JM. Standards for Simulation. Anaesthesia. 2008;63 :1281–1284 McGaghie WC, Issenberg SB, Petrusa ER, Scalese RJ. A critical review of simulation-based medical education research: 2003–2009. Med Educ 2010;44 :5063